Preparation method of bio-based epoxy resin / carbon fiber composite material
By developing a method of compositeing of hexahydrohomotriazine-containing bio-based hyperbranched epoxy resin with carbon fiber, the toxicity and non-degradability problems of petroleum-based epoxy resin in the prior art are solved, and the preparation of high-strength and high-modulus bio-based epoxy resin/carbon fiber composite materials is realized, which has environmental protection and economic advantages.
Patent Information
- Application Number
- CN202411906407.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the prior art, the physiological toxicity and non-degradability of petroleum-based epoxy resins lead to safety and environmental problems in their applications, and it is difficult to completely replace carbon fiber composite materials prepared from petroleum-based materials.
A hexahydrohomotriazine-containing biobased hyperbranched epoxy resin was developed, and a biobased epoxy resin/carbon fiber composite material with high strength and high modulus was prepared by combining with a bio-based linear epoxy resin and carbon fiber. The method includes performing a thiol-olefin click reaction on a carbon fiber cloth to modify the surface, and synthesizing a hyperbranched polymer through a click reaction triggered by ultraviolet light, and finally performing hot pressing curing to prepare the composite material.
The high strength and high modulus characteristics of bio-based epoxy resin/carbon fiber composite materials are achieved, and the dependence on petroleum-based materials is reduced. The process is simple, the reaction conditions are mild, and the raw material cost is low, which has environmental protection and economic advantages.
Smart Images

Figure BDA0005204471670000011 
Figure BDA0005204471670000012 
Figure BDA0005204471670000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a method for preparing a bio-based epoxy resin / carbon fiber composite material. Background Art
[0002] Carbon fiber reinforced thermosetting polymer composites have the advantages of high specific strength, excellent mechanical properties, and chemical corrosion resistance. They are increasingly used in aerospace, power cables, wind power generation and other fields. However, most thermosetting resins such as bisphenol A epoxy resins are produced from petroleum raw materials. With the rising prices of fossil fuels, the need to protect health and the environment, and the potential for bio-based resources to prepare thermosetting materials with performance comparable to that of petroleum-based materials (ACS Sustainable Chem. Eng. 2016, 4, 4328-4339). Therefore, how to replace petroleum-based epoxy resins with thermosetting resins synthesized from bio-based resources has attracted the attention of more and more researchers.
[0003] The previous applicant team prepared a degradable hyperbranched epoxy resin (patents ZL201810386063.3, ZL201810387204.3), and a degradable bio-based hyperbranched epoxy resin (patents ZL202010396471.4, ZL201611044769.9), which is used to strengthen and toughen bisphenol A epoxy resin, but bisphenol A epoxy resin has physiological toxicity and comes from petroleum. To solve this problem, the previous applicant team prepared a bio-based linear epoxy resin (patent ZL202111664373.5). Therefore, the development of bio-based resources with rich raw material sources as the basis for synthesizing bio-based hyperbranched epoxy resins and bio-based linear epoxy resins, and using them to prepare carbon fiber composite materials is the fundamental way to solve the problems in this field. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin-carbon fiber composite material and a preparation method thereof.
[0005] The present invention solves the above technical problems with the following technical solutions:
[0006] Technical solution 1: A hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, the structural formula of which is shown in general formula (1):
[0007]
[0008] The structure of R is as follows:
[0009]
[0010] Wherein n is a natural number of 1 to 5; the mercaptoalkyl acid and the alcohol undergo an esterification reaction to form -CO- and -O- to -COO-, and the thiol and olefin compounds undergo a thiol-olefin click reaction to form -CS- and one of -R', -R", and -R"' to -CS-R'(R",R"').
[0011] Wherein, R', R", and R'" are the same or different and are independently represented by the structure of general formula (2), general formula (3) or general formula (4):
[0012]
[0013] General formula (2) General formula (3) General formula (4)
[0014] Wherein, X is one or more of the following structures:
[0015]
[0016] The structure of R1 is as follows:
[0017]
[0018] The structure of R2 is as follows:
[0019]
[0020] R3 is one or more of the following structures:
[0021]
[0022] The number average molecular weight of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin is 2000-28000 g / mol, and the epoxy value is 0.09-0.19 mol / 100 g.
[0023] Technical solution 2: A method for preparing a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, comprising the following steps:
[0024] The bio-based diamine and maleic anhydride are mixed evenly in a water-carrying agent, a catalyst is added under a nitrogen atmosphere, the reaction is stirred at 110-160°C for 8-16h, and the solid is precipitated in an ice-water bath and filtered to obtain a bio-based bismaleimide monomer; phenylglycinol, an aldehyde compound and a mercaptoalkyl acid are mixed evenly in an organic solvent, the reaction is stirred at 25-100°C for 4-16h under a nitrogen atmosphere, and the organic solvent is removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; the bio-based bismaleimide monomer, the bio-based hexahydro-s-triazine monomer and the organic solvent are heated to 400 ℃. 00W-800W ultraviolet light is used under a photoinitiator to obtain a terminal thiol hyperbranched polymer through a click reaction for 30-100min, and the number average molecular weight is 1600-26000g / mol; then an olefin epoxy compound is added and a click reaction is carried out for 60-120min with a power of 400W-800W ultraviolet light, and the organic solvent is removed by rotary evaporation to obtain a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, with a number average molecular weight of 2000-28000g / mol and an epoxy value of 0.09-0.19mol / 100g;
[0025] The molar ratio of the bio-based diamine to maleic anhydride is 1:(2.10-2.50); the molar ratio of the phenylglycinol, aldehyde compound and mercaptoalkyl acid is 1:(1-2):(1-2); the molar ratio of the bio-based bismaleimide to the bio-based hexahydro-s-triazine is 1:(1.05-2); the molar ratio of the bio-based hexahydro-s-triazine monomer to the alkenyl epoxy compound is 1:(1.09-2);
[0026] The bio-based diamine is one or more of 2,5-furandimethylamine, 1,4-cyclohexanedimethylamine and isophoronediamine; the mercaptoalkyl acid is HS(CH2) n COOH, n is a natural number of 1 to 5; the aldehyde compound is one or more of formaldehyde solution, trioxymethylene and polyformaldehyde (polymerization degree n is a natural number of 2 to 100); the alkenyl epoxy compound is one or more of 1,2-epoxy-5-hexene, allyl glycidyl ether and 2,3-epoxypropyl acrylate.
[0027] The water-carrying agent is one or more of toluene, benzene, 1,4-dioxane, xylene and N,N-dimethylformamide, and the mass of the water-carrying agent added is 5-15 times the mass of maleic anhydride; the catalyst is one or more of n-butyl titanate, tetraisopropyl titanate or p-toluenesulfonic acid, and the mass of the catalyst added is 1.5-3.0% of the mass of maleic anhydride; the organic solvent for synthesizing the bio-based hexahydro-s-triazine monomer is one or more of acetone, chloroform, ethyl acetate, dichloromethane, tetrahydrofuran, toluene, xylene, 1,4-dioxane, and the mass of the organic solvent added is 5-18 times the mass of phenylglycinol; The photoinitiator is one or more of p-aminopropiophenone, 1-hydroxycyclohexyl phenyl ketone, 4-dimethylaminopyridine, benzophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and the mass of the added photoinitiator is 1.0-3.5% of the mass of the bio-based hexahydro-s-triazine. The organic solvent for synthesizing the terminal thiol hyperbranched polymer is one or more of dichloromethane, tetrahydrofuran, water, N,N-dimethylformamide, xylene, toluene and 1,4-dioxane, and the mass of the added organic solvent is 2-5 times the mass of the bio-based hexahydro-s-triazine monomer.
[0028] Technical solution three: A bio-based epoxy resin composite material, the composite material comprising the above-mentioned hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin and a bio-based linear epoxy resin. The epoxy value of the bio-based linear epoxy resin is 0.10-0.90 mol / 100g, preferably 0.48-0.55 mol / 100g.
[0029] The hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, the bio-based linear epoxy resin and the curing agent are uniformly mixed and then poured into a mold for thermal curing to obtain the composite material; the curing temperature is 50-200° C. and the curing time is 4-8 hours; the curing agent is one or more of 4,4'-methylenebiscyclohexylamine, 4,4'-diaminodiphenylmethane, diethylenetriamine, isophoronediamine (IPDA), 2,2'-diaminodiphenyl sulfide (DOA) and 4,4'-diaminodiphenyl sulfide (BAS).
[0030] The mass ratio of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin to the bio-based linear epoxy resin is (0.5-1):(9-9.5). The mass of the added curing agent is calculated according to the following formula: n*molecular weight of the curing agent*epoxy value of the epoxy resin in the system*mass of the epoxy resin in the system / number of active hydrogens on the curing agent, wherein n=0.01-0.02.
[0031] Technical solution four: A bio-based epoxy resin / carbon fiber composite material, wherein the composite material is prepared by blending the above-mentioned bio-based hyperbranched epoxy resin containing hexahydro-s-triazine or the bio-based hyperbranched epoxy resin containing hexahydro-s-triazine prepared by the above-mentioned method with a bio-based linear epoxy resin and filling them in a carbon fiber cloth, and then laminating and curing them; before curing, the carbon fiber cloth is modified by a thiol-olefin click reaction of the terminal thiol hyperbranched polymer prepared by the above-mentioned method to obtain a surface functionalized carbon fiber cloth.
[0032] Furthermore, the preparation method comprises the following steps: immersing the carbon fiber cloth in a mixed solution of the terminal thiol hyperbranched polymer prepared by the above method, an organic solvent and a photoinitiator, and performing a thiol-olefin click reaction for 40-80 minutes under the action of the photoinitiator using ultraviolet light with a power of 400W-800W; after the reaction is completed, taking out the carbon fiber cloth, drying it at 50-80°C for 8-24h, and obtaining a surface functionalized carbon fiber cloth; placing the surface functionalized carbon fiber cloth into a mold, and evenly applying the above hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin or a mixture of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin prepared by the above method, a bio-based linear epoxy resin and a curing agent on the surface functionalized carbon fiber cloth, hot pressing and curing for 3-6h under the conditions of 1-10MPa and 80-180°C, and taking it out after cooling to room temperature, and obtaining a bio-based epoxy resin / carbon fiber composite material.
[0033] The mass ratio of the carbon fiber cloth to the terminal mercapto hyperbranched polymer is 1:(0.50-0.83); the mass ratio of the surface functionalized carbon fiber cloth, the hexahydrotriazine-containing bio-based hyperbranched epoxy resin, and the bio-based linear epoxy resin is (0.90-0.95):(0.01-0.05):(0.45-0.50).
[0034] The carbon fiber cloth is one of commercially available T300, T700 and T800; the photoinitiator is one or more of p-aminopropiophenone, 4-dimethylaminopyridine, benzophenone, 1-hydroxycyclohexyl benzophenone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and the mass of the added photoinitiator is 1.0-3.5% of the mass of the carbon fiber cloth; the organic solvent is tetrahydrofuran, 1,4-dioxane, ethyl acetate, anhydrous ethanol, methanol, dimethyl sulfoxide, toluene, dimethoxybenzene ... One or more of toluene, acetone, chloroform, N,N-dimethylformamide and dichloromethane, whose mass is 5 to 30 times the mass of the carbon fiber cloth; the curing agent is one or more of 4,4'-methylenebiscyclohexylamine, 4,4'-diaminodiphenylmethane, diethylenetriamine, isophoronediamine, 2,2'-diaminodiphenyl sulfide and 4,4'-diaminodiphenyl sulfide, and the mass of the added curing agent is calculated according to the following formula: n*molecular weight of curing agent*epoxy value of epoxy resin in the system*mass of epoxy resin in the system / number of active hydrogens on the curing agent, wherein n=0.01-0.02.
[0035] Technical solution 5: A degradation and recycling method for a bio-based epoxy resin / carbon fiber composite material, comprising the following steps: immersing the bio-based epoxy resin / carbon fiber composite material in an acidic hydrogen peroxide solution, degrading it at 60-80°C for 6-12 hours to obtain a carbon fiber cloth and a degradation solution; rinsing the carbon fiber cloth with acetone and drying it at 50-70°C for 10-24 hours to obtain a regenerated carbon fiber cloth; and then recycling the regenerated carbon fiber cloth instead of the carbon fiber cloth;
[0036] The acidic hydrogen peroxide solution is a hydrogen peroxide solution of phosphoric acid or hydrochloric acid, the acid concentration is 0.10-1.00 mol / L, the solvent in the acidic hydrogen peroxide solution is one or more of tetrahydrofuran, 1,4-dioxane, acetone, water and N,N-dimethylformamide, the mass proportion of hydrogen peroxide in the acidic hydrogen peroxide solution is 50%-90%; the mass ratio of the bio-based epoxy resin / carbon fiber composite material to the acidic hydrogen peroxide solution is 1:(2-5).
[0037] Compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:
[0038] (1) The present invention introduces a degradable hexahydro-s-triazine structure and an imide bond into the structure of a hyperbranched epoxy resin to achieve a degradable function after curing the epoxy resin;
[0039] (2) The bio-based hyperbranched epoxy resin of the present invention has the advantages of hyperbranched polymers and has obvious strengthening and toughening functions for bio-based linear epoxy resins, and is expected to be widely used in the field of strengthening and toughening epoxy resins;
[0040] (3) The preparation process of the bio-based hyperbranched epoxy resin / bio-based linear epoxy resin composite material of the present invention is simple, the reaction conditions are relatively mild, the reaction time is short, and the raw material cost is low;
[0041] (4) The bio-based epoxy resin / carbon fiber composite material of the present invention has the characteristics of high strength and high modulus, and is expected to be used in the fields of power cables, aerospace, etc.;
[0042] (5) The preparation process of the bio-based epoxy resin / carbon fiber composite material of the present invention is simple, the reaction conditions are relatively mild, the reaction time is short, and the raw material cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the infrared spectrum of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin prepared in Example 7-9. -1 The absorption peak at -CH2- is located at 1725cm -1 The absorption peak at 1692 cm is attributed to the stretching vibration of -C=ON-. -1 The absorption peak at 1383 cm is attributed to the stretching vibration of -C=OO-. -1 The absorption peak at 925cm -1 The absorption peak at is the absorption peak of the epoxy group. DETAILED DESCRIPTION
[0044] The method of the present invention is further described below in conjunction with specific examples, but these examples should not limit the scope of protection of the present invention in any way.
[0045] The raw material carbon fiber cloth used in the embodiments and comparative examples is one of the commercially available T300, T700 and T800, wherein T300 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF220T, T700 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF200T, and T800 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF260T.
[0046] The bio-based linear epoxy resin used in the embodiment is any one of furandicarboxylic acid diglycidyl ether (DGF), ferulic acid-based epoxy resin (FEP) and vanillyl alcohol-based bio-epoxy resin (DGEVA), wherein furandicarboxylic acid diglycidyl ether (DGF) is prepared with reference to RSC Adv., 2015, 5, 15930, with a number average molecular weight of 266.08 g / mol and an epoxy value of 0.48 mol / 100 g; ferulic acid-based epoxy resin (FEP) is prepared with reference to patent ZL202111664373.5, with a number average molecular weight of 306.11 g / mol and an epoxy value of 0.51 mol / 100 g; vanillyl alcohol-based bio-epoxy resin (DGEVA) is prepared with reference to ACSSustainable Prepared by Chem.Eng.2020,8,11215-11223, the number average molecular weight is 266.12 g / mol, and the epoxy value is 0.55 mol / 100 g.
[0047] Among them, the number average molecular weight is obtained by gel permeation chromatography (GPC), based on the penetration behavior of the hyperbranched polymer in the gel, by measuring the ratio of the penetration time and the standard sample; the epoxy value is obtained by the hydrochloric acid-acetone method, using hydrochloric acid to react with the epoxy group, and then determining the amount of residual hydrochloric acid by titration, and then knowing the amount of hydrochloric acid reacting with the epoxy group, thereby calculating the amount of the epoxy group to obtain the epoxy value.
[0048] Example 1 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, wherein the steps are as follows:
[0049] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0050] 0.10 mol (12.61 g) of 2,5-furandimethylamine and 0.25 mol (24.52 g) of maleic anhydride were mixed evenly in 63.05 g of xylene and 63.05 g of 1,4-dioxane, and 0.39 g of p-toluenesulfonic acid was added under nitrogen atmosphere and stirred at 110°C for 16 h. After precipitation in an ice-water bath for 12 h, the solid was filtered to obtain a bio-based bismaleimide monomer. 0.10 mol (13.71 g) of phenylglycinol, 0.10 mol (8.12 g, 37%) of formaldehyde aqueous solution and 0.15 mol (15.90 g) of mercaptopropionic acid were mixed evenly in 68.55 g of dichloromethane and 68.55 g of tetrahydrofuran, and stirred at 25°C for 16 h under nitrogen atmosphere. The organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer. In the presence of 1-hydroxycyclohexyl phenyl ketone, 0.01 mol (2.86 g) of bio-based bismaleimide monomer, 0.02 mol (14.24 g) of bio-based hexahydro-s-triazine monomer and 28.48 g of 1,4-dioxane were subjected to a click reaction for 100 min using ultraviolet light with a power of 400 W to obtain a terminal thiol hyperbranched polymer (BISPI-4); then 0.04 mol (3.93 g) of 1,2-epoxy-5-hexene was added and click-reacted with ultraviolet light with a power of 400 W for 120 min, and 1,4-dioxane was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (BIEP-4); GPC test showed that its molecular weight was about 2133 g / mol, and the epoxy value obtained by titration was 0.19 mol / 100 g. The results are shown in Tables 1 and 2.
[0051] (2) Research on the properties of bio-based epoxy resin
[0052] First, 1.40 g of diethylenetriamine, 9.25 g of furandicarboxylic acid diglycidyl ether (DGF) and 0.75 g of BIEP-4 were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 h, 130° C. for 1 h, and 170° C. for 2 h to obtain the BIEP-4 / DGF composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0053] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0054] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 1.50 g of terminal thiol bio-based hyperbranched polymer (BISPI-4), 15 g of ethyl acetate and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 400 W for 80 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 1-TCF. The 1-TCF was taken out and dried at 50°C for 24 h. The dried 3.00 g of 1-TCF was put into a mold, and a mixture of 1.39 g of DGF, 0.11 g of BIEP-4 and 0.21 g of diethylenetriamine was evenly applied to the 1-TCF in the mold, and hot-pressed and cured at 120°C for 4 h under 3 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0055] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0056] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 20.00g of 1.00mol / L phosphoric acid hydrogen peroxide acetone solution (hydrogen peroxide: acetone = 9:1, m / m), and degraded at 80℃ for 6h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 70℃ for 10h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.50g of terminal thiol bio-based hyperbranched polymer (BISPI-4), 15g of ethyl acetate and 0.03g of p-aminophenylacetone, and irradiated with ultraviolet light with a power of 400W for 80min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 1-rTCF, and 1-rTCF was taken out and dried at 50℃ for 24h; 3.00g of 1-rTCF after drying was put into a mold, and 1.39g of DGF, 0.11g A mixture of BIEP-4 and 0.21 g of diethylenetriamine was evenly applied to 1-rTCF in the mold and hot-pressed at 120 °C for 4 h under 3 MPa conditions. After the hot pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0057] Example 2 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0058] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0059] 0.10 mol (12.61 g) of 2,5-furandimethylamine and 0.23 mol (22.55 g) of maleic anhydride were mixed evenly in 120.61 g of benzene and 120.61 g of N,N-dimethylformamide. 0.26 g of n-butyl titanate and 0.26 g of tetraisopropyl titanate were added under nitrogen atmosphere and stirred at 160 ° C for 8 h. After precipitation in an ice-water bath for 18 h, the solid was filtered to obtain bio-based bismaleimide. Imine monomer; 0.10 mol (13.71 g) of phenylglycinol, 0.15 mol (12.17 g, 37%) of formaldehyde aqueous solution and 0.15 mol (15.90 g) of mercaptopropionic acid were mixed evenly in 123.39 g of acetone and 123.39 g of chloroform, stirred at 100 ° C for 4 h under nitrogen atmosphere, and the organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; in 0.07 g In the presence of 1-hydroxycyclohexyl phenyl ketone and 0.07 g of p-aminopropiophenone, 0.01 mol (2.86 g) of bio-based bismaleimide monomer, 0.013 mol (7.25 g) of bio-based hexahydro-s-triazine monomer and 21.75 g of N,N-dimethylformamide were subjected to a click reaction for 30 min using ultraviolet light at a power of 800 W to obtain a terminal thiol hyperbranched polymer (BISPI-6); 0.02 mol (2.56 g) of 2,3-epoxypropyl acrylate was then added and the reaction was carried out using ultraviolet light at a power of 800 W for 60 min, and N,N-dimethylformamide was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (BIEP-6); the molecular weight thereof was about 4568 g / mol as measured by GPC, and the epoxy value obtained by titration was 0.13 mol / 100 g, as shown in Tables 1 and 2.
[0060] (2) Research on the properties of bio-based epoxy resin
[0061] First, the 0.50 g BIEP-6, 3.08 g 4,4'-methylenebiscyclohexylamine, and 9.50 g DGF were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 50° C. for 1 h, 130° C. for 1 h, 170° C. for 2 h, and 180° C. for 2 h to obtain the BIEP-6 / DGF composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0062] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0063] 3.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 2.00 g of terminal thiol bio-based hyperbranched polymer (BISPI-6), 20 g of N,N-dimethylformamide, 15 g of tetrahydrofuran, 15 g of 1,4-dioxane, 0.03 g of p-aminopropiophenone and 0.03 g of 1-hydroxycyclohexylphenyl ketone, and irradiated with ultraviolet light with a power of 400 W for 80 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 2-TCF. The 2-TCF was taken out and dried at 70°C for 18 h. The dried 3.00 g of 2-TCF was put into a mold, and 1.425 g of DGF, 0.075 g of BIEP-6 and 0.46 g of The mixture of 4,4'-methylenebiscyclohexylamine was evenly applied to 2-TCF in the mold, and hot-pressed and cured at 80°C for 3 h and 120°C for 3 h under 1 MPa conditions. After hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0064] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0065] 4.00 g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00 g of 0.10 mol / L phosphoric acid hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12 h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24 h to obtain regenerated carbon fiber cloth; then 3.00 g of the regenerated carbon fiber cloth was completely immersed in 2.00 g of BISPI-6 (prepared in Example 2), 20 g of N,N-dimethylformamide, 15 g of tetrahydrofuran, 15 g of A mixed solution of 1,4-dioxane, 0.03g p-aminopropiophenone and 0.03g 1-hydroxycyclohexyl phenyl ketone was irradiated with ultraviolet light at a power of 400W for 80min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 2-rTCF. The 2-rTCF was taken out and dried at 70°C for 18h. 3.00g of 2-rTCF after drying was put into a mold, and a mixture of 1.425g DGF, 0.075g BIEP-6 and 0.46g 4,4'-methylenebiscyclohexylamine was evenly applied to the 2-rTCF in the mold. The mixture was hot-pressed and cured at 80°C for 3h and at 120°C for 3h under 1MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0066] Example 3 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0067] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0068] 0.10 mol (12.61 g) of 2,5-furandimethylamine and 0.25 mol (24.52 g) of maleic anhydride were mixed evenly in 122.60 g of toluene and 122.60 g of N,N-dimethylformamide, 0.32 g of p-toluenesulfonic acid and 0.32 g of n-butyl titanate were added under nitrogen atmosphere, stirred and reacted at 135°C for 12 h, and the solid was filtered after precipitation in an ice-water bath for 24 h to obtain a bio-based bismaleimide monomer; 0.10 mol (13.71 g) of benzylglycinol, 0.20 mol (12.00 g) of polyformaldehyde (polymerization degree is 2) and 0.10 mol (14.80 g) of mercaptohexanoic acid were mixed evenly in 164.52 g of ethyl acetate, stirred and reacted at 60°C for 10 h under nitrogen atmosphere, and the organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; 0.26 g of In the presence of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 0.01mol (2.86g) of bio-based bismaleimide monomer, 0.0105mol (8.80g) of bio-based hexahydro-s-triazine monomer and 37.40g of dichloromethane were subjected to a click reaction with ultraviolet light at a power of 600W for 60min to obtain a terminal thiol hyperbranched polymer (BISPI-24); then 0.0114mol (1.30g) of allyl glycidyl ether was added and the reaction was carried out with ultraviolet light at a power of 600W for 80min, and the dichloromethane was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (BIEP-24); the molecular weight thereof was about 26000g / mol as measured by GPC, and the epoxy value obtained by titration was 0.09mol / 100g, and the results are shown in Tables 1 and 2.
[0069] (2) Research on the properties of bio-based epoxy resin
[0070] First, 1.00 g BIEP-24, 2.57 g 4,4'-diaminodiphenylmethane, and 9.00 g DGF were mixed in a 125°C oil bath for 2 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 60°C for 1 h, 80°C for 3 h, 130°C for 1 h, 170°C for 2 h, and 200°C for 1 h to obtain the BIEP-24 / DGF composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0071] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0072] 3.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 2.50 g of terminal thiol bio-based hyperbranched polymer (BISPI-24), 30 g of acetone, 30 g of chloroform, 30 g of dichloromethane and 0.10 g of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and irradiated with ultraviolet light with a power of 600 W for 60 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 3-TCF. The 3-TCF was taken out and dried at 80° C. for 8 h. The dried 3.00 g of 3-TCF was put into a mold, and 1.35 g of DGF, 0.15 g of BIEP-24 and 0.44 g of The mixture of 4,4'-diaminodiphenylmethane was evenly applied to 3-TCF in the mold and hot-pressed and cured at 120 °C for 3 h under 10 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0073] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0074] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 12.00g of 0.50mol / L phosphoric acid in hydrogen peroxide N,N-dimethylformamide solution (hydrogen peroxide: N,N-dimethylformamide = 6:4, m / m), and degraded at 70℃ for 8h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 60℃ for 20h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in 2.50g of terminal thiol bio-based hyperbranched polymer (BISPI-24), 30g of acetone, 30g of chloroform, 30g of dichloromethane and 0.10g of The mixed solution of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was irradiated with ultraviolet light at a power of 600 W for 60 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 3-rTCF. The 3-rTCF was taken out and dried at 80 ° C for 8 h. 3.00 g of 3-rTCF after drying was put into a mold, and a mixture of 1.35 g DGF, 0.15 g BIEP-24 and 0.44 g 4,4'-diaminodiphenylmethane was evenly applied to the 3-rTCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa. After hot pressing, the bio-based epoxy resin-carbon fiber composite material was obtained after cooling to room temperature. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0075] Example 4 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0076] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0077] 0.10 mol (14.22 g) of 1,4-cyclohexanedimethylamine and 0.25 mol (24.52 g) of maleic anhydride were mixed evenly in 63.05 g of xylene and 63.05 g of 1.4-dioxane, and 0.39 g of p-toluenesulfonic acid was added under nitrogen atmosphere and stirred at 110°C for 16 h. After precipitation in an ice-water bath for 12 h, the solid was filtered to obtain the bio-based bismaleimide monomer; 0.10 mol (13.71 g) of phenylglycinol, 0.10 mol (8.12 g, 37%) of formaldehyde aqueous solution and 0.15 mol (15.90 g) of mercaptopropionic acid were mixed evenly in 68.55 g of dichloromethane and 68.55 g of tetrahydrofuran, and stirred at 25°C for 16 h under nitrogen atmosphere. The organic solvent was removed by rotary evaporation to obtain the bio-based hexahydro-s-triazine monomer; 0.14 g of 0.01 mol (3.02 g) of bio-based bismaleimide monomer, 0.02 mol (14.24 g) of bio-based hexahydro-s-triazine monomer and 28.48 g of 1,4-dioxane were reacted by ultraviolet light with a power of 400 W for 100 min to obtain a terminal thiol hyperbranched polymer (BPSPI-4) in the presence of 1-hydroxycyclohexyl benzophenone; then 0.04 mol (3.93 g) of 1,2-epoxy-5-hexene was added and clicked with ultraviolet light with a power of 400 W for 120 min, and 1,4-dioxane was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (BPEP-4); GPC test showed that its molecular weight was about 2054 g / mol, and the epoxy value obtained by titration was 0.19 mol / 100 g. The results are shown in Tables 1 and 2.
[0078] (2) Research on the properties of bio-based epoxy resin
[0079] First, 1.40 g of diethylenetriamine, 9.25 g of FEP and 0.75 g of BPEP-4 were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 h, 130° C. for 1 h, and 170° C. for 2 h to obtain the BPEP-4 / FEP composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0080] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0081] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 1.50 g of terminal thiol bio-based hyperbranched polymer (BPSPI-4), 15 g of ethyl acetate and 0.03 g of 1-hydroxycyclohexyl phenyl ketone, and irradiated with ultraviolet light with a power of 400 W for 80 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 4-TCF. The 4-TCF was taken out and dried at 50°C for 24 h. The dried 3.00 g of 4-TCF was put into a mold, and a mixture of 1.39 g of FEP, 0.11 g of BPEP-4 and 0.21 g of diethylenetriamine was evenly applied to the 4-TCF in the mold, and hot-pressed and cured at 120°C for 4 h under 3 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and the tensile strength and flexural strength thereof are shown in Table 4.
[0082] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0083] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 12.00g of 0.50mol / L phosphoric acid hydrogen peroxide 1,4-dioxane solution (hydrogen peroxide: 1,4-dioxane = 6:4, m / m), and degraded at 70°C for 8h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 60°C for 20h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.50g of terminal thiol bio-based hyperbranched polymer (BPSPI-4), 15g of ethyl acetate and 0.03g of 1-hydroxycyclohexyl phenyl ketone, and irradiated with ultraviolet light with a power of 400W for 80min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 4-rTCF, and 4-rTCF was taken out and dried at 50°C for 24h; 3.00g of the dried carbon fiber cloth was taken out and dried at 50°C for 24h. 4-rTCF was put into the mold, and a mixture of 1.39g FEP, 0.11g BPEP-4 and 0.21g diethylenetriamine was evenly applied to the 4-rTCF in the mold, and hot-pressed and cured at 120°C for 4h under 3MPa conditions; after hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0084] Example 5 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0085] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0086] 0.10 mol (14.22 g) of 1,4-cyclohexanedimethylamine and 0.23 mol (22.55 g) of maleic anhydride were dissolved in 120.61 g of benzene and 120.61 g of Mix evenly in N,N-dimethylformamide, add 0.26g n-butyl titanate and 0.26g tetraisopropyl titanate under nitrogen atmosphere, stir and react at 160℃ for 8h, precipitate in ice water bath for 15h and filter the solid to obtain bio-based bismaleimide monomer; mix 0.10mol (13.71g) benzylglycinol, 0.15mol (12.17g, 37%) formaldehyde aqueous solution and 0.15mol (15.90g) mercaptopropionic acid in 123.39g acetone and 123.39g chloroform, stir and react at 100℃ for 4h under nitrogen atmosphere, and remove the organic solvent by rotary evaporation to obtain bio-based hexahydro-s-triazine monomer; add 0.07g In the presence of 1-hydroxycyclohexyl phenyl ketone and 0.07g of p-aminopropiophenone, 0.01mol (3.02g) of bio-based bismaleimide monomer, 0.013mol (7.25g) of bio-based hexahydro-s-triazine monomer and 21.75g of N,N-dimethylformamide were subjected to a click reaction for 30min with ultraviolet light at a power of 800W to obtain a terminal thiol hyperbranched polymer (BPSPI-6); then 0.02mol (2.56g) of 2,3-epoxypropyl acrylate was added and the reaction was carried out with ultraviolet light at a power of 800W for 60min, and N,N-dimethylformamide was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (BPEP-6); the molecular weight thereof was about 4400g / mol as measured by GPC, and the epoxy value obtained by titration was 0.13mol / 100g, and the results are shown in Tables 1 and 2.
[0087] (2) Research on the properties of bio-based epoxy resin
[0088] First, the 0.50 g BPEP-6, 3.08 g 4,4'-methylenebiscyclohexylamine, and 9.50 g FEP were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 50° C. for 1 h, 130° C. for 1 h, 170° C. for 2 h, and 180° C. for 2 h to obtain the BPEP-6 / FEP composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0089] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0090] 3.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 2.00 g of terminal thiol bio-based hyperbranched polymer (BPSPI-6), 20 g of N,N-dimethylformamide, 15 g of tetrahydrofuran, 15 g of 1,4-dioxane, 0.03 g of p-aminopropiophenone and 0.03 g of 1-hydroxycyclohexylphenyl ketone, and irradiated with ultraviolet light with a power of 800 W for 40 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 5-TCF. The 5-TCF was taken out and dried at 70°C for 18 h. The dried 3.00 g of 5-TCF was put into a mold, and 1.425 g of FEP, 0.075 g of BPEP-6 and 0.46 g of The mixture of 4,4'-methylenebiscyclohexylamine was evenly applied to 5-TCF in the mold, and hot-pressed and cured at 80°C for 3 h and 120°C for 3 h under 1 MPa conditions. After hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0091] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0092] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00g of 0.10mol / L phosphoric acid hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in 2.00g of terminal thiol bio-based hyperbranched polymer (BPSPI-6), 20g of N,N-dimethylformamide, 15g of tetrahydrofuran, 15g of 1,4-dioxane, 0.03g of p-aminopropiophenone and 0.03g of The mixed solution of 1-hydroxycyclohexyl phenyl ketone was irradiated with ultraviolet light at a power of 800 W for 40 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 5-rTCF. The 5-rTCF was taken out and dried at 70 ° C for 18 h. 3.00 g of 5-rTCF after drying was put into a mold, and a mixture of 1.425 g FEP, 0.075 g BPEP-6 and 0.46 g 4,4'-methylenebiscyclohexylamine was evenly applied to the 5-rTCF in the mold. The mixture was hot-pressed and cured at 80 ° C for 3 h and 120 ° C for 3 h under 1 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0093] Example 6 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0094] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0095] 0.10 mol (14.22 g) 1,4-cyclohexanedimethylamine and 0.25 mol (24.52 g) maleic anhydride were mixed evenly in 122.60 g toluene and 122.60 g N,N-dimethylformamide, 0.32 g p-toluenesulfonic acid and 0.32 g n-butyl titanate were added under nitrogen atmosphere, stirred and reacted at 135 ° C for 12 h, and the solid was filtered after precipitation in an ice water bath for 12 h to obtain the bio-based bismaleimide monomer; 0.10 mol (13.71 g) benzylglycinol, 0.20 mol (12.00 g) polyformaldehyde (degree of polymerization is 2) and 0.10 mol (14.80 g) mercaptohexanoic acid were mixed in 164.52 g acetic acid. The mixture was uniformly mixed with ethyl ester, stirred and reacted at 60 ° C under nitrogen atmosphere for 10 hours, and the organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; 0.01 mol (3.02 g) of bio-based bismaleimide monomer, 0.0105 mol (8.80 g) of bio-based hexahydro-s-triazine monomer and 37.40 g of N,N-dimethylformamide was subjected to a click reaction with ultraviolet light at a power of 600 W for 60 minutes to obtain a terminal thiol hyperbranched polymer (BPSPI-24); then 0.0114 mol (1.30 g) of allyl glycidyl ether was added and the reaction was carried out with ultraviolet light at a power of 600 W for 80 minutes, and N,N-dimethylformamide was removed by rotary evaporation to obtain a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin (BPEP-24); GPC test showed that the molecular weight was about 27900 g / mol, and the epoxy value obtained by titration was 0.09 mol / 100 g. The results are shown in Tables 1 and 2.
[0096] (2) Research on the properties of bio-based epoxy resin
[0097] First, 1.00 g of BPEP-24, 2.78 g of 4,4'-diaminodiphenylmethane, and 9.00 g of FEP were mixed in a 125°C oil bath for 2 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 60°C for 1 h, 80°C for 3 h, 130°C for 1 h, 170°C for 2 h, and 200°C for 1 h to obtain the BPEP-24 / FEP composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0098] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0099] 3.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 2.50 g of terminal thiol bio-based hyperbranched polymer (BPSPI-24), 30 g of acetone, 30 g of chloroform, 30 g of dichloromethane and 0.10 g of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and irradiated with ultraviolet light with a power of 600 W for 60 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 6-TCF. The 6-TCF was taken out and dried at 80° C. for 8 h. The dried 3.00 g of 6-TCF was put into a mold, and 1.35 g of FEP, 0.15 g of BPEP-24 and 0.44 g of The mixture of 4,4'-diaminodiphenylmethane was evenly applied to 6-TCF in the mold and hot-pressed and cured at 120 °C for 3 h under 10 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0100] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0101] 4.00 g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00 g of 0.10 mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60 ° C for 12 h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50 ° C for 24 h to obtain regenerated carbon fiber cloth; then 3.00 g of regenerated carbon fiber cloth was completely immersed in 2.50 g of terminal thiol bio-based hyperbranched polymer (BPSPI-24), 30 g of acetone, 30 g of chloroform, 30 g of dichloromethane and 0.10 g of The mixed solution of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was irradiated with ultraviolet light at a power of 600 W for 60 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 6-rTCF. The 6-rTCF was taken out and dried at 80 ° C for 8 h. 3.00 g of 6-rTCF after drying was put into a mold, and a mixture of 1.35 g FEP, 0.15 g BPEP-24 and 0.44 g 4,4'-diaminodiphenylmethane was evenly applied to the 6-rTCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa. After hot pressing, the bio-based epoxy resin-carbon fiber composite material was obtained after cooling to room temperature. The mechanical properties of the composite material were tested by a universal testing machine, and the tensile strength is shown in Table 4.
[0102] Example 7 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0103] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0104] 0.10 mol (17.02 g) of isophorone diamine and 0.25 mol (24.52 g) of maleic anhydride were mixed evenly in 63.05 g of xylene and 63.05 g of 1,4-dioxane, 0.39 g of p-toluenesulfonic acid was added under nitrogen atmosphere and stirred at 110°C for 16 h, and the solid was filtered after precipitation in an ice-water bath for 12 h to obtain the bio-based bismaleimide monomer; 0.10 mol (13.71 g) of phenylglycinol, 0.10 mol (8.12 g, 37%) of formaldehyde aqueous solution and 0.15 mol (15.90 g) of mercaptopropionic acid were mixed evenly in 68.55 g of dichloromethane and 68.55 g of tetrahydrofuran, stirred at 25°C for 16 h under nitrogen atmosphere, and the organic solvent was removed by rotary evaporation to obtain the bio-based hexahydro-s-triazine monomer; 0.14 g of In the presence of 1-hydroxycyclohexyl phenyl ketone, 0.01 mol (3.30 g) of bio-based bismaleimide monomer, 0.02 mol (14.24 g) of bio-based hexahydro-s-triazine monomer and 28.48 g of 1,4-dioxane were subjected to a click reaction for 100 min under ultraviolet light with a power of 400 W to obtain a terminal thiol hyperbranched polymer (MSPI-4); then 0.04 mol (3.93 g) of 1,2-epoxy-5-hexene was added and the reaction was carried out under ultraviolet light with a power of 400 W for 120 min, and 1,4-dioxane was removed by rotary evaporation to obtain a bio-based hyperbranched epoxy resin containing hexahydro-s-triazine (MIEP-4); GPC test showed that its molecular weight was about 2100 g / mol, and the epoxy value obtained by titration was 0.19 mol / 100 g. The results are shown in Tables 1 and 2.
[0105] (2) Research on the properties of bio-based epoxy resin
[0106] First, 1.40 g of diethylenetriamine, 9.25 g of DGEVA and 0.75 g of MIEP-4 were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 h, 130° C. for 1 h, and 170° C. for 2 h to obtain the MIEP-4 / DGEVA composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0107] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0108] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 1.50 g of terminal thiol bio-based hyperbranched polymer (MSPI-4), 15 g of ethyl acetate and 0.10 g of p-aminopropiophenone, and irradiated with ultraviolet light of 400 W for 80 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, i.e., 7-TCF. The 7-TCF was taken out and dried at 50°C for 24 h. 3.00 g of 7-TCF after drying was put into a mold, and a mixture of 1.39 g of DGEVA, 0.11 g of MIEP-4 and 0.21 g of diethylenetriamine was evenly applied to the 7-TCF in the mold, and hot-pressed and cured at 120°C for 4 h under 3 MPa. After hot pressing, the bio-based epoxy resin-carbon fiber composite material was obtained after cooling to room temperature. The mechanical properties of the composite material were tested by a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0109] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0110] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00g of 0.10mol / L phosphoric acid hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60℃ for 12h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50℃ for 24h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.50g of terminal thiol bio-based hyperbranched polymer (MSPI-4), 15g of ethyl acetate and 0.10g of p-aminophenylacetone, and irradiated with ultraviolet light with a power of 400W for 80min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 7-rTCF, and 7-rTCF was taken out and dried at 50℃ for 24h; 3.00g of 7-rTCF after drying was put into a mold, and 1.39g of DGEVA, 0.11g A mixture of MIEP-4 and 0.21 g of diethylenetriamine was evenly applied to 7-rTCF in the mold and hot-pressed at 120 °C for 4 h under 3 MPa conditions. After the hot pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0111] Example 8 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0112] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0113] 0.10 mol (17.02 g) of isophorone diamine and 0.23 mol (22.55 g) of maleic anhydride were mixed evenly in 120.61 g of benzene and 120.61 g of N, N-dimethylformamide, 0.26 g of n-butyl titanate and 0.26 g of tetraisopropyl titanate were added under nitrogen atmosphere and stirred at 160°C for 8 h, and the solid was filtered after precipitation in an ice-water bath for 12 h to obtain a bio-based bismaleimide monomer; 0.10 mol (13.71 g) of phenylglycinol, 0.15 mol (12.17 g, 37%) of formaldehyde aqueous solution and 0.15 mol (15.90 g) of mercaptopropionic acid were mixed evenly in 123.39 g of acetone and 123.39 g of chloroform, stirred at 100°C for 4 h under nitrogen atmosphere, and the organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; 0.12 g of In the presence of 1-hydroxycyclohexyl phenyl ketone and 0.12g of p-aminopropiophenone, 0.01mol (3.30g) of bio-based bismaleimide monomer, 0.013mol (7.25g) of bio-based hexahydro-s-triazine monomer and 21.75g of N,N-dimethylformamide were subjected to a click reaction for 30min with ultraviolet light at a power of 800W to obtain a terminal thiol hyperbranched polymer (MSPI-6); then 0.02mol (2.56g) of 2,3-epoxypropyl acrylate was added and the reaction was carried out with ultraviolet light at a power of 800W for 60min, and N,N-dimethylformamide was removed by rotary evaporation to obtain a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin (MIEP-6); GPC test showed that the molecular weight was about 4400g / mol, and the epoxy value obtained by titration was 0.13mol / 100g, and the results are shown in Tables 1 and 2.
[0114] (2) Research on the properties of bio-based epoxy resin
[0115] First, the 0.50 g MIEP-6, 3.08 g 4,4'-methylenebiscyclohexylamine, and 9.50 g DGEVA were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 50° C. for 1 h, 130° C. for 1 h, 170° C. for 2 h, and 180° C. for 2 h to obtain the MIEP-6 / DGEVA composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0116] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0117] 3.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 2.00 g of terminal thiol bio-based hyperbranched polymer (MSPI-6), 20 g of N,N-dimethylformamide, 15 g of tetrahydrofuran, 15 g of 1,4-dioxane, 0.03 g of p-aminopropiophenone and 0.03 g of 1-hydroxycyclohexylphenyl ketone, and irradiated with ultraviolet light with a power of 400 W for 40 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 8-TCF. The 8-TCF was taken out and dried at 70°C for 18 h. The dried 3.00 g of 8-TCF was put into a mold, and 1.425 g of DGEVA, 0.075 g of MIEP-6 and 0.46 g of The mixture of 4,4'-methylenebiscyclohexylamine was evenly applied to 8-TCF in the mold, and hot-pressed and cured at 80°C for 3 h and 120°C for 3 h under 1 MPa conditions. After hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0118] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0119] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00g of 0.10mol / L phosphoric acid hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in 2.00g of terminal thiol bio-based hyperbranched polymer (MSPI-6), 20g of N,N-dimethylformamide, 15g of tetrahydrofuran, 15g of 1,4-dioxane, 0.03g of p-aminopropiophenone and 0.03g of The mixed solution of 1-hydroxycyclohexyl phenyl ketone was irradiated with ultraviolet light at a power of 400 W for 40 minutes to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 8-rTCF. The 8-rTCF was taken out and dried at 70°C for 18 hours. 3.00g of 8-rTCF after drying was put into a mold, and a mixture of 1.425g DGEVA, 0.075g MIEP-6 and 0.46g 4,4'-methylenebiscyclohexylamine was evenly applied to the 8-rTCF in the mold. The mixture was hot-pressed and cured at 80°C for 3 hours and at 120°C for 3 hours under 1MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0120] Example 9 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0121] (1) Synthesis of bio-based hyperbranched epoxy resin containing hexahydrotriazine
[0122] 0.10 mol (17.02 g) of isophorone diamine and 0.25 mol (24.52 g) of maleic anhydride were mixed evenly in 122.60 g of toluene and 122.60 g of N,N-dimethylformamide. 0.32 g of p-toluenesulfonic acid and 0.32 g of n-butyl titanate were added under nitrogen atmosphere and stirred at 135 ° C for 12 h. After precipitation in an ice-water bath for 12 h, the solid was filtered to obtain the bio-based bismaleimide monomer. ; 0.10 mol (13.71 g) of phenylglycinol, 0.20 mol (12.00 g) of paraformaldehyde (degree of polymerization: 2) and 0.10 mol (14.80 g) of mercaptohexanoic acid were mixed evenly in 164.52 g of ethyl acetate, stirred at 60 ° C for 10 h under nitrogen atmosphere, and the organic solvent was removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; 0.12 g of p-aminopropiophenone and 0.12 g of In the presence of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 0.01mol (3.30g) of bio-based bismaleimide monomer, 0.0105mol (8.80g) of bio-based hexahydro-s-triazine monomer and 37.40g of N,N-dimethylformamide were subjected to a click reaction for 60min with ultraviolet light at a power of 600W to obtain a terminal thiol hyperbranched polymer (MSPI-24); then 0.0114mol (1.30g) of allyl glycidyl ether was added and the reaction was carried out with ultraviolet light at a power of 600W for 80min, and N,N-dimethylformamide was removed by rotary evaporation to obtain a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin (MIEP-24); GPC test showed that the molecular weight was about 26800g / mol, and the epoxy value obtained by titration was 0.09mol / 100g, and the results are shown in Tables 1 and 2.
[0123] (2) Research on the properties of bio-based epoxy resin
[0124] First, 1.00 g of MIEP-24, 2.93 g of 4,4'-diaminodiphenylmethane, and 9.00 g of DGEVA were mixed in a 125°C oil bath for 2 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 60°C for 1 h, 80°C for 3 h, 130°C for 1 h, 170°C for 2 h, and 200°C for 1 h to obtain the MIEP-24 / DGEVA composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0125] (3) Preparation of bio-based epoxy resin-carbon fiber composites
[0126] 3.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 2.50 g of terminal thiol bio-based hyperbranched polymer (MSPI-24), 30 g of acetone, 30 g of chloroform, 30 g of dichloromethane and 0.10 g of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and irradiated with ultraviolet light with a power of 600 W for 60 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 9-TCF. The 9-TCF was taken out and dried at 80° C. for 8 h. The dried 3.00 g of 9-TCF was put into a mold, and 1.35 g of DGEVA, 0.15 g of MIEP-24 and 0.44 g of The mixture of 4,4'-diaminodiphenylmethane was evenly applied to 9-TCF in the mold and hot-pressed and cured at 120 °C for 3 h under 10 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0127] (4) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0128] 4.00g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00g of 0.10mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24h to obtain regenerated carbon fiber cloth; then 3.00g of regenerated carbon fiber cloth was completely immersed in 2.50g of terminal thiol bio-based hyperbranched polymer (MSPI-24), 30g of acetone, 30g of chloroform, 30g of dichloromethane and 0.10g of The mixed solution of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was irradiated with ultraviolet light at a power of 600 W for 60 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 9-rTCF. The 9-rTCF was taken out and dried at 80 ° C for 8 h. 3.00 g of 9-rTCF after drying was put into a mold, and a mixture of 1.35 g DGEVA, 0.15 g MIEP-24 and 0.44 g 4,4'-diaminodiphenylmethane was evenly applied to the 9-rTCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa. After hot pressing, the bio-based epoxy resin-carbon fiber composite material was obtained after cooling to room temperature. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0129] Embodiments 10, 11-I, 11-II, 11-III, 11-IV A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, wherein the steps are as follows:
[0130] The methods of Examples 10, 11-I, 11-II, 11-III and 11-IV are the same as those of Example 9, except that the curing agent and the amount of the curing agent are changed. Specifically:
[0131] (1) Research on the properties of bio-based epoxy resin
[0132] Example 10, the curing agent is diethylenetriamine, and the amount used is 1.58g;
[0133] Example 11-Ⅰ, the curing agent is 4,4'-methylenebiscyclohexylamine, and the amount used is 3.11g;
[0134] Example 11-II, the curing agent is isophorone diamine, and the amount used is 2.47 g;
[0135] Example 11-III, the curing agent is 2,2'-diaminodiphenyl sulfide, and the amount used is 3.11g;
[0136] Example 11-IV, the curing agent is 4,4'-diaminodiphenyl sulfide, and the amount used is 3.11 g.
[0137] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 3.
[0138] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0139] Example 10, the curing agent is diethylenetriamine, and the amount used is 0.24g;
[0140] Example 11-Ⅰ, the curing agent is 4,4'-methylenebiscyclohexylamine, and the amount used is 0.47g;
[0141] Example 11-II, the curing agent is isophorone diamine, and the amount used is 0.37g;
[0142] Example 11-III, the curing agent is 2,2'-diaminodiphenyl sulfide, and the amount used is 0.47g;
[0143] Example 11-IV, the curing agent is 4,4'-diaminodiphenyl sulfide, and the amount used is 0.47 g.
[0144] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0145] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0146] The types and amounts of the curing agents in Examples 10, 11-I, 11-II, 11-III, and 11-IV are the same as those in step (2).
[0147] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0148] Example 12 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0149] (1) Research on the properties of bio-based epoxy resin
[0150] First, 1.00 g of MIEP-6 (prepared in Example 8), 2.96 g of 4,4'-diaminodiphenylmethane, and 9.00 g of DGEVA were mixed in a 125° C. oil bath for 2 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 60° C. for 1 h, 80° C. for 3 h, 130° C. for 1 h, 170° C. for 2 h, and 200° C. for 1 h to obtain the MIEP-6 / DGEVA-2 composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0151] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0152] Example 12 The method for treating carbon fiber is the same as that of Example 8, except that T700 is replaced by T800, and the surface functionalized carbon fiber cloth is named 12-TCF. 3.00 g of 12-TCF after drying is put into a mold, and a mixture of 1.35 g of DGEVA, 0.15 g of MIEP-6 and 0.44 g of 4,4'-diaminodiphenylmethane is evenly applied to the 12-TCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa conditions; after hot pressing, it is cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material are tested using a universal testing machine, and the tensile strength and flexural strength are shown in Table 4.
[0153] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0154] 4.00 g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00 g of 0.10 mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12 h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24 h to obtain regenerated carbon fiber cloth; then 3.00 g of regenerated carbon fiber cloth was completely immersed in 2.50 g of terminal thiol bio-based hyperbranched polymer (MSPI-6, prepared in Example 8), 30 g of acetone, 30 g of chloroform, 30 g of dichloromethane and 0.10 g of The mixed solution of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was irradiated with ultraviolet light at a power of 600 W for 60 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 12-rTCF. The 12-rTCF was taken out and dried at 80 ° C for 8 h. 3.00 g of 12-rTCF after drying was put into a mold, and a mixture of 1.35 g of DGEVA, 0.15 g of MIEP-6 and 0.44 g of 4,4'-diaminodiphenylmethane was evenly applied to the 12-rTCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa. After hot pressing, the bio-based epoxy resin-carbon fiber composite material was obtained after cooling to room temperature. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0155] Example 13 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0156] (1) Research on the properties of bio-based epoxy resin
[0157] First, 1.00 g of MIEP-4 (prepared in Example 7), 2.94 g of 4,4'-diaminodiphenylmethane, and 9.00 g of DGEVA were mixed in a 125° C. oil bath for 2 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 60° C. for 1 h, 80° C. for 3 h, 130° C. for 1 h, 170° C. for 2 h, and 200° C. for 1 h to obtain the MIEP-4 / DGEVA-2 composite resin. The mechanical properties of the composite resin were tested using a universal testing machine, and the results are shown in Table 3.
[0158] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0159] Example 13 The method for treating carbon fiber is the same as that of Example 7, except that T300 is replaced by T800, and the surface functionalized carbon fiber cloth is named 13-TCF; 3.00 g of 13-TCF after drying is put into a mold, and a mixture of 1.35 g of DGEVA, 0.15 g of MIEP-4 and 0.44 g of 4,4'-diaminodiphenylmethane is evenly applied to the 7-TCF in the mold, and hot-pressed and cured at 120°C for 3 h under 10 MPa conditions; after hot pressing, the mixture is cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material, and the mechanical properties of the composite material are tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0160] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0161] 4.00 g of bio-based epoxy resin-carbon fiber composite material was immersed in 8.00 g of 0.10 mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60°C for 12 h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24 h to obtain regenerated carbon fiber cloth; then 3.00 g of regenerated carbon fiber cloth was completely immersed in 2.50 g of terminal thiol bio-based hyperbranched polymer (MSPI-4, prepared in Example 7), 30 g of acetone, 30 g of chloroform and 30 g of dichloromethane and 0.10 g of The mixed solution of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was irradiated with ultraviolet light at a power of 600 W for 60 min to carry out thiol-olefin click reaction to obtain surface functionalized carbon fiber cloth, namely 13-rTCF. The 13-rTCF was taken out and dried at 80 ° C for 8 h. 3.00 g of 13-rTCF after drying was put into a mold, and a mixture of 1.35 g of DGEVA, 0.15 g of MIEP-4 and 0.44 g of 4,4'-diaminodiphenylmethane was evenly applied to the 13-rTCF in the mold, and hot-pressed and cured at 120 ° C for 3 h under 10 MPa. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0162] Example 14 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0163] Example 14 is the same as Example 3, except that the bio-based linear epoxy resin and the amount of curing agent used are changed. Specifically:
[0164] (1) Research on the properties of bio-based epoxy resin
[0165] In Example 14, the bio-based linear epoxy resin is DGEVA, and the amount used is the same as that in Example 3, and the amount of curing agent used is 2.94 g of 4,4'-diaminodiphenylmethane.
[0166] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 3.
[0167] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0168] In Example 14, the bio-based linear epoxy resin is DGEVA, and its dosage, curing agent and its dosage are the same as those in Example 3.
[0169] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0170] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0171] In Example 14, the bio-based linear epoxy resin is DGEVA, and its dosage, curing agent and its dosage are the same as those in Example 3.
[0172] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0173] Example 15 A bio-based epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:
[0174] The method of Example 15 is the same as that of Example 6, except that the bio-based linear epoxy resin and the amount of curing agent used are changed. Specifically:
[0175] (1) Research on the properties of bio-based epoxy resin
[0176] In Example 15, the bio-based linear epoxy resin is DGEVA, and the amount used is the same as that in Example 6, and the amount of curing agent used is 2.94 g of 4,4'-diaminodiphenylmethane.
[0177] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 3.
[0178] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0179] In Example 15, the bio-based linear epoxy resin is DGEVA, and its dosage, curing agent and its dosage are the same as those in Example 6.
[0180] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0181] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0182] In Example 15, the bio-based linear epoxy resin is DGEVA, and its dosage, curing agent and its dosage are the same as those in Example 6.
[0183] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0184] Comparative Example 1
[0185] (1) Research on the properties of bio-based epoxy resin
[0186] First, the 2.82 g of 4,4'-diaminodiphenylmethane and 10.00 g of DGF were mixed in a 120° C. oil bath for 1 hour until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 hour, 130° C. for 1 hour, and 170° C. for 2 hours to obtain the DGF resin. The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3.
[0187] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0188] 3.00 g of carbon fiber cloth (T800, PCF) was put into the mold, and a mixture of 1.50 g of DGF and 0.42 g of 4,4'-diaminodiphenylmethane was evenly applied to the PCF in the mold. The mixture was hot-pressed and cured at 120 °C for 4 h under 3 MPa conditions. After the hot-pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0189] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0190] 4.00g of the composite material was immersed in 20.00g of 1.00mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 9:1, m / m), and degraded at 80℃ for 6h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 70℃ for 10h to obtain recycled carbon fiber cloth, namely 1-rPCF; then 3.00g of 1-rPCF after drying was put into a mold, and a mixture of 1.50g DGF and 0.42g 4,4'-diaminodiphenylmethane was evenly applied to the 1-rPCF in the mold, and hot-pressed at 120℃ for 4h under 3MPa conditions; after hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material, and the mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0191] Comparative Example 2
[0192] (1) Research on the properties of bio-based epoxy resin
[0193] First, the 3.00 g 4,4'-diaminodiphenylmethane and 10.00 g FEP were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 h, 130° C. for 1 h, and 170° C. for 2 h to obtain the FEP resin. The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3.
[0194] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0195] 3.00 g of carbon fiber cloth (T800, PCF) was placed in a mold, and a mixture of 1.50 g of FEP and 0.45 g of 4,4'-diaminodiphenylmethane was evenly applied to the PCF in the mold. The mixture was hot-pressed and cured at 120 °C for 4 h under 3 MPa conditions. After the hot-pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0196] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0197] 4.00g of the composite material was immersed in 12.00g of 0.50mol / L phosphoric acid in a hydrogen peroxide 1,4-dioxane solution (hydrogen peroxide: 1,4-dioxane = 6:4, m / m), and degraded at 70°C for 8h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 60°C for 20h to obtain a regenerated carbon fiber cloth, namely 2-rPCF; then 3.00g of the dried 2-rPCF was put into a mold, and a mixture of 1.50g of FEP and 0.45g of 4,4'-diaminodiphenylmethane was evenly applied to the 2-rPCF in the mold, and hot-pressed at 120°C for 4h under 3MPa conditions; after hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material, and the mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0198] Comparative Examples 3-I, 3-II, 3-III, 3-IV, 3-V, 3-VI
[0199] In comparative examples 3-Ⅰ, 3-II, 3-III, 3-IV, 3-V and 3-VI, only the curing agent and its amount are different. Specifically:
[0200] (1) Research on the properties of bio-based epoxy resin
[0201] First, the 3.24 g of 4,4'-diaminodiphenylmethane and 10.00 g of DGEVA were mixed in a 120°C oil bath for 1 hour until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80°C for 1 hour, 130°C for 1 hour, and 170°C for 2 hours to obtain the DGEVA composite resin. The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3.
[0202] Example 3-Ⅰ, curing agent and dosage: 4,4'-diaminodiphenylmethane 3.24g;
[0203] Example 3-II, curing agent and dosage: diethylenetriamine 1.66g;
[0204] Example 3-III, curing agent and dosage: 4,4'-methylenebiscyclohexylamine 3.40g;
[0205] Example 3-IV, curing agent and dosage is 2.47g of isophorone diamine;
[0206] Example 3-V, curing agent and dosage: 2,2'-diaminodiphenyl sulfide 3.40g;
[0207] Example 3-VI, curing agent and dosage: 4,4'-diaminodiphenyl sulfide 3.40g;
[0208] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 3.
[0209] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0210] 3.00 g of carbon fiber cloth (T800, PCF) was placed in a mold, and a mixture of 1.50 g of DGEVA and 0.48 g of 4,4'-diaminodiphenylmethane was evenly applied to the PCF in the mold. The mixture was hot-pressed and cured at 120 °C for 4 h under 3 MPa conditions. After the hot-pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine. The tensile strength and flexural strength are shown in Table 4.
[0211] Example 3-Ⅰ, curing agent and dosage: 4,4'-diaminodiphenylmethane 0.48g;
[0212] Example 3-II, curing agent and dosage is 0.25g of diethylenetriamine;
[0213] Example 3-III, curing agent and dosage: 4,4'-methylenebiscyclohexylamine 0.51g;
[0214] Example 3-IV, curing agent and dosage is 0.41g of isophorone diamine;
[0215] Example 3-V, curing agent and dosage: 2,2'-diaminodiphenyl sulfide 0.51g;
[0216] Example 3-VI, curing agent and dosage: 4,4'-diaminodiphenyl sulfide 0.51g;
[0217] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0218] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0219] 4.00g of the composite material was immersed in 8.00g of 0.10mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 5:5, m / m), and degraded at 60℃ for 12h to obtain carbon fiber cloth and degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50℃ for 24h to obtain regenerated carbon fiber cloth, namely 3-rPCF; then 3.00g of 3-rPCF after drying was put into a mold, and a mixture of 1.50g DGEVA and 0.48g 4,4'-diaminodiphenylmethane was evenly applied to the 3-rPCF in the mold, and hot-pressed and cured at 120℃ for 4h under 3MPa conditions; after hot pressing, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material, and the mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0220] The types and amounts of curing agents in Comparative Examples 3-Ⅰ, 3-II, 3-III, 3-IV, 3-V and 3-VI are the same as those in step (2).
[0221] The mechanical properties of the composite resin were tested using a universal testing machine. The results are shown in Table 4.
[0222] Comparative Example 4
[0223] (1) Research on the properties of bio-based epoxy resin
[0224] First, the 0.53 g of 4,4'-diaminodiphenylmethane and 10.00 g of BIEP-24 (prepared in Example 3) were mixed in a 120° C. oil bath for 1 h until uniform, and then poured into a 10×80 mm mold. The curing procedure was 80° C. for 1 h, 130° C. for 1 h, and 170° C. for 2 h to obtain the BIEP-24 composite resin. The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3.
[0225] (2) Preparation of bio-based epoxy resin-carbon fiber composites
[0226] 3.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 1.50 g of terminal thiol bio-based hyperbranched polymer (BISPI-24, prepared in Example 3), 15 g of ethyl acetate and 0.03 g of 1-hydroxycyclohexyl phenyl ketone, and irradiated with ultraviolet light with a power of 600 W for 40 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 3-TCF. The 3-TCF was taken out and dried at 50° C. for 24 h. The dried 3.00 g of 3-TCF was put into a mold, and a mixture of 1.50 g of BIEP-24 and 0.08 g of 4,4'-diaminodiphenylmethane was evenly applied to the 3-TCF in the mold, and hot-pressed and cured at 120° C. for 4 h under 3 MPa conditions. After the hot pressing was completed, the mixture was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and the tensile strength and flexural strength thereof were shown in Table 4.
[0227] (3) Degradation and recycling of bio-based epoxy resin-carbon fiber composites
[0228] 4.00g of the composite material was immersed in 20.00g of 1.00mol / L phosphoric acid in hydrogen peroxide tetrahydrofuran solution (hydrogen peroxide: tetrahydrofuran = 9:1, m / m), and degraded at 80°C for 6h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 70°C for 10h to obtain a regenerated carbon fiber cloth; then 3.00g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.50g of terminal thiol bio-based hyperbranched polymer (BISPI-24), 15g of ethyl acetate and 0.03g of 1-hydroxycyclohexyl phenyl ketone, and irradiated with ultraviolet light at a power of 600W for 40min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 3-rTCF, and the 3-rTCF was taken out and dried at 50°C for 24h; the dried 3.00g of 3-rTCF was put into a mold, and 1.50g BIEP-24 and 0.08g The mixture of 4,4'-diaminodiphenylmethane was evenly applied to 3-rTCF in the mold and hot-pressed and cured at 120 °C for 4 h under 3 MPa conditions. After the hot pressing was completed, it was cooled to room temperature and taken out to obtain a bio-based epoxy resin-carbon fiber composite material. The mechanical properties of the composite material were tested using a universal testing machine, and its tensile strength is shown in Table 4.
[0229] Comparative Example 5
[0230] The method of Comparative Example 5 is the same as that of Comparative Example 4, except that the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin and the thiol-terminated bio-based hyperbranched polymer are replaced. In Comparative Example 5, the bio-based hyperbranched epoxy resin and the thiol-terminated bio-based hyperbranched polymer are BPEP-24 and BPSPI-24 prepared in Example 6.
[0231] The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3. The mechanical properties of the bio-based epoxy resin-carbon fiber composite material were tested using a universal testing machine, and the tensile strength and flexural strength are shown in Table 4.
[0232] Comparative Example 6
[0233] The method of Comparative Example 6 is the same as that of Comparative Example 4, except that the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin and the thiol-terminated bio-based hyperbranched polymer are replaced. In Comparative Example 6, the bio-based hyperbranched epoxy resin and the thiol-terminated bio-based hyperbranched polymer are MIEP-24 and MSPI-24 prepared in Example 9.
[0234] The mechanical properties of the resin were tested using a universal testing machine, and the results are shown in Table 3. The mechanical properties of the bio-based epoxy resin-carbon fiber composite material were tested using a universal testing machine, and the tensile strength and flexural strength are shown in Table 4.
[0235] Table 1 Number average molecular weight of bio-based thiol-terminated hyperbranched polymers prepared in Examples 1 to 9
[0236] Example Product Name Number average molecular weight of thiol-terminated hyperbranched polymer (g / mol) Example 1 BISPI-4 1700 Example 2 BISPI-6 3800 Example 3 BISPI-24 23300 Example 4 BPSPI-4 1600 Example 5 BPSPI-6 3700 Example 6 BPSPI-24 25200 Example 7 MSPI-4 1700 Example 8 MSPI-6 3800 Example 9 MSPI-24 24100
[0237] Table 2 Number average molecular weight and epoxy value of bio-based hyperbranched epoxy resins prepared in Examples 1 to 9
[0238] Example Product Name Hyperbranched epoxy resin number average molecular weight (g / mol) Epoxy value (mol / 100g) Example 1 BIEP-4 2100 0.19 Example 2 BIEP-6 4600 0.13 Example 3 BIEP-24 26000 0.09 Example 4 BPEP-4 2100 0.19 Example 5 BPEP-6 4400 0.13 Example 6 BPEP-24 27900 0.09 Example 7 MIEP-4 2100 0.19 Example 8 MIEP-6 4400 0.13 Example 9 MIEP-24 26800 0.09
[0239] Table 3 Performance test results of bio-based epoxy resin composite resins prepared in Examples 1 to 15
[0240]
[0241]
[0242] Table 4 Performance test results of bio-based epoxy resin / carbon fiber composites prepared in Examples 1 to 15
[0243]
[0244]
[0245] 1) From the test results in Table 1, we can see that:
[0246] The number average molecular weight of the terminal thiol hyperbranched polymers obtained in Examples 1-3, 4-6 and 7-9 of the present invention gradually increases with the increase of the number of terminal thiol groups; when the number of terminal thiol groups is 24, the number average molecular weight reaches the maximum value.
[0247] 2) From the test results in Table 2, we can see that:
[0248] The number average molecular weight of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resins obtained in Examples 1-3, 4-6 and 7-9 of the present invention gradually increases with the increase in the number of terminal epoxy groups; when the number of terminal epoxy groups is 24, the number average molecular weight reaches the maximum.
[0249] The hexahydro-s-triazine-containing bio-based hyperbranched epoxy resins obtained in Examples 1-3 and 7-9 of the present invention have an epoxy value that gradually decreases as the number of terminal epoxy groups increases; when the number of terminal epoxy groups is 4, the epoxy value is the largest, and the epoxy values are all 0.19 mol / 100g.
[0250] 3) From the test results in Table 3 and Table 4, we can see that:
[0251] The bio-based epoxy resin composite resin obtained in Examples 1-3, 4-6 and 7-9 of the present invention found that different numbers of terminal epoxy, different curing agents and different mass fractions of bio-based hyperbranched epoxy resins will lead to different tensile strength and flexural strength of the composite resin, wherein when the number of terminal epoxy is 24, the curing agent is 4,4'-diaminodiphenylmethane, and the mass fraction of the bio-based hyperbranched epoxy resin added is 10%, the tensile strength and flexural strength of the bio-based epoxy resin composite resin reach the maximum value. In addition, by comparing different bio-based epoxy resin-carbon fiber composite materials, it is also found that different types of carbon fiber cloth, different bio-based epoxy resins, different mass ratios of carbon fiber to terminal thiol hyperbranched polymers and different mass fractions of bio-based hyperbranched epoxy resins will lead to different tensile strength and flexural strength of the composite material, wherein when the carbon fiber cloth is T800, the mass ratio of carbon fiber to terminal thiol hyperbranched polymer is 3.0:2.5, and the mass fraction of the bio-based hyperbranched epoxy resin added is 10%, the tensile strength and flexural strength of the composite material reach the maximum value.
[0252] In Examples 1, 4 and 7 of the present invention, the bio-based epoxy resin composite resins obtained are different due to the different structures of the bio-based diamines, resulting in different tensile strengths and flexural strengths of the bio-based epoxy resin composite resins, wherein when the bio-based diamine is isophorone diamine, the tensile strength and flexural strength reach the maximum value. The reason is that the bio-based diamine structure in Example 1 contains a five-membered ring, while the bio-based diamine structures in Examples 4 and 7 contain a six-membered ring, so the tensile strength and flexural strength of the bio-based epoxy resin composite resin in Example 1 are lower than those in Examples 4 and 7; the bio-based diamine structure in Example 7 contains a shorter linear structure than that in Example 4, so the tensile strength and flexural strength of the bio-based epoxy resin composite resin in Example 7 are higher than those in Example 4. The same reason also affects the difference in tensile strength and flexural strength of the bio-based epoxy resin-carbon fiber composite material.
[0253] In Examples 9, 10, 11-Ⅰ, 11-II, 11-III and 11-IV of the present invention, the same bio-based epoxy resin, the same number of terminal epoxy groups, the same carbon fiber cloth, the same mass ratio of carbon fiber to terminal mercapto hyperbranched polymer and the same mass fraction of bio-based hyperbranched epoxy resin, different curing agents will lead to different tensile strengths and flexural strengths of bio-based epoxy resin composites and bio-based epoxy resin-carbon fiber composites. When the curing agent is 4,4'-diaminodiphenylmethane, the tensile strength and flexural strength of the bio-based epoxy resin composite reach the maximum values, which are 97±4MPa and 167±4MPa, respectively, which are 40.58% and 40.34% higher than those of Comparative Example 3-Ⅰ; the tensile strength and flexural strength of the bio-based epoxy resin-carbon fiber composite material reach the maximum values, which are 919±14MPa and 946±13MPa, respectively, which are 27.29% and 30.48% higher than those of Comparative Example 3-Ⅰ. Comparing Example 9, Example 10, Example 11-Ⅰ, 11-II, 11-III, 11-IV with Comparative Examples 3-Ⅰ, 3-II, 3-III, 3-IV, 3-V, 3-VI, it can be seen that when using different curing agents, the bio-based hyperbranched epoxy resin MIEP-24 has obvious strengthening and toughening functions for the bio-based linear epoxy resin DGEVA. Comparing Examples 7 and 8 with Comparative Examples 3-II and 3-III, it can also be seen that when using different curing agents, the bio-based hyperbranched epoxy resins MIEP-4 and MIEP-6 have obvious strengthening and toughening functions for the bio-based linear epoxy resin DGEVA.
[0254] In Example 9 and Example 12-13 of the present invention, the same curing agent, the same bio-based epoxy resin, the same carbon fiber cloth, the same mass ratio of carbon fiber to terminal thiol hyperbranched polymer and the same mass fraction of bio-based hyperbranched epoxy resin, the different number of terminal epoxy will lead to different tensile strength and flexural strength of bio-based epoxy resin composite resin and bio-based epoxy resin-carbon fiber composite material, wherein when the number of terminal epoxy is 24, the tensile strength and flexural strength of the composite resin reach the maximum value, which are 97±4MPa and 167±4MPa respectively; the tensile strength and flexural strength of the bio-based epoxy resin-carbon fiber composite material reach the maximum value, which are 919±14MPa and 946±13MPa respectively. The composite resins and composite materials prepared in Example 9 and Example 14-15 also have significantly improved tensile strength and flexural strength relative to Comparative Example 6.
[0255] In Examples 9 and 14-15 of the present invention, the same curing agent, the same bio-based linear epoxy resin, the same carbon fiber cloth, the same mass ratio of carbon fiber to terminal thiol hyperbranched polymer, the same number of terminal epoxy groups and the same mass fraction of bio-based hyperbranched epoxy resin, different bio-based hyperbranched epoxy resins will lead to different tensile strengths and flexural strengths of bio-based epoxy resin composites and bio-based epoxy resin-carbon fiber composites. The main reason is that the diamines for synthesizing the hyperbranched epoxy resin are different. When the diamine is isophorone diamine, the tensile strength and flexural strength of the bio-based epoxy resin composite and the bio-based epoxy resin-carbon fiber composite both reach the maximum value.
[0256] The bio-based epoxy resin composite resin and bio-based epoxy resin-carbon fiber composite material prepared in Examples 9, 14 and 15 have significantly improved tensile strength and flexural strength compared with Comparative Examples 6, 4 and 5.
[0257] In Examples 14, 3, 15 and 6 of the present invention, only the bio-based linear epoxy resin is different. The tensile strength and flexural strength properties of the prepared bio-based epoxy resin composite resin and bio-based epoxy resin-carbon fiber composite material are comparable, with DGEVA being better.
[0258] The acidic hydrogen peroxide solution degradation system provided by the present invention can realize the degradation, recycling and reuse of bio-based epoxy resin / carbon fiber composite materials. The tensile strength of the composite material prepared by recycling the carbon fiber cloth recycled from the composite material is compared with the tensile strength of the original composite material, indicating that the tensile strength of the carbon fiber cloth recycled by degradation, recycling and regeneration has no obvious decrease, and the retention rate is relatively high, all above 88%.
[0259] In summary, the composite use of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin and the bio-based linear epoxy resin of the present invention can significantly improve the tensile strength and flexural strength of the bio-based epoxy resin-carbon fiber composite material, achieve the purpose of achieving the strength of high-end carbon fiber with low-grade carbon fiber, and realize the recycling of carbon fiber at the same time, and the tensile strength of the recycled carbon fiber cloth composite material does not decrease significantly.
[0260] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, characterized in that: Its structural formula is shown in general formula (1): The structure of R is as follows: n is a natural number from 1 to 5, and -CO- and -CH2O- in R are connected; Wherein, R', R", and R'" are the same or different and are independently represented by the structure of general formula (2), general formula (3) or general formula (4): General formula (2) General formula (3) General formula (4) Wherein, X is one or more of the following structures: The structure of R1 is as follows: The structure of R2 is as follows: R3 is one or more of the following structures: The number average molecular weight of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin is 2000-28000 g / mol, and the epoxy value is 0.09-0.19 mol / 100 g.
2. The method for preparing the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin according to claim 1, characterized in that: The following steps are involved: The bio-based diamine and maleic anhydride are mixed evenly in a water-carrying agent, a catalyst is added under a nitrogen atmosphere, the mixture is stirred and reacted at 110-160°C for 8-16 hours, and the mixture is precipitated in an ice-water bath and the solid is filtered to obtain a bio-based bismaleimide monomer; phenylglycinol, an aldehyde compound and a mercaptoalkyl acid are mixed evenly in an organic solvent, the mixture is stirred and reacted at 25-100°C for 4-16 hours under a nitrogen atmosphere, and the solvent is removed by rotary evaporation to obtain a bio-based hexahydro-s-triazine monomer; the bio-based bismaleimide monomer and the bio-based hexahydro-s-triazine monomer are mixed. The body and the organic solvent are subjected to a click reaction for 30-100 minutes under a photoinitiator with a power of 400W-800W ultraviolet light to obtain a terminal thiol hyperbranched polymer; then an olefin epoxy compound is added and subjected to a click reaction for 60-120 minutes with a power of 400W-800W ultraviolet light, and the organic solvent is removed by rotary evaporation to obtain a hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin with a number average molecular weight of 2000-28000 g / mol and an epoxy value of 0.09-0.19 mol / 100g.
3. The preparation method according to claim 2, characterized in that: The bio-based diamine is one or more of 2,5-furandimethylamine, 1,4-cyclohexanedimethylamine and isophoronediamine; the mercaptoalkyl acid is HS(CH2) n COOH, n is a natural number of 1 to 5; the aldehyde compound is one or more of formaldehyde solution, trioxymethylene and polyformaldehyde; the alkenyl epoxy compound is one or more of 1,2-epoxy-5-hexene, allyl glycidyl ether and 2,3-epoxypropyl acrylate.
4. The preparation method according to claim 2, characterized in that: The molar ratio of the bio-based diamine to maleic anhydride is 1:(2.10-2.50); the molar ratio of the phenylglycinol, aldehyde compound and mercaptoalkyl acid is 1:(1-2):(1-2); the molar ratio of the bio-based bismaleimide to bio-based hexahydro-s-triazine is 1:(1.05-2); the molar ratio of the bio-based hexahydro-s-triazine monomer to the alkenyl epoxy compound is 1:(1.09-2).
5. The preparation method according to claim 2, characterized in that: The water-carrying agent is one or more of toluene, benzene, 1,4-dioxane, xylene and N,N-dimethylformamide, and the mass of the water-carrying agent added is 5-15 times the mass of maleic anhydride; the catalyst is one or more of n-butyl titanate, tetraisopropyl titanate or p-toluenesulfonic acid, and the mass of the catalyst added is 1.5-3.0% of the mass of maleic anhydride; the organic solvent for synthesizing the bio-based hexahydro-s-triazine monomer is one or more of acetone, chloroform, ethyl acetate, dichloromethane, tetrahydrofuran, toluene, xylene, 1,4-dioxane, and the mass of the organic solvent added is 5-18 times the mass of phenylglycinol; The photoinitiator is one or more of p-aminopropiophenone, 1-hydroxycyclohexyl phenyl ketone, 4-dimethylaminopyridine, benzophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and the mass of the added photoinitiator is 1.0-3.5% of the mass of the bio-based hexahydro-s-triazine. The organic solvent for synthesizing the terminal thiol hyperbranched polymer is one or more of dichloromethane, tetrahydrofuran, water, N,N-dimethylformamide, xylene, toluene and 1,4-dioxane, and the mass of the added organic solvent is 2-5 times the mass of the bio-based hexahydro-s-triazine monomer.
6. A bio-based epoxy resin composite material, characterized in that: The composite material comprises the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin according to claim 1 or the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin prepared by any method described in claims 2-5 and a bio-based linear epoxy resin, wherein the epoxy value of the bio-based linear epoxy resin is 0.10-0.90 mol / 100g.
7. The bio-based epoxy resin composite material according to claim 6, characterized in that: The hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin, the bio-based linear epoxy resin and the curing agent are uniformly mixed, and then poured into a mold for thermal curing to obtain the composite material; the curing agent is one or more of 4,4'-methylenebiscyclohexylamine, 4,4'-diaminodiphenylmethane, diethylenetriamine, isophoronediamine, 2,2'-diaminodiphenyl sulfide and 4,4'-diaminodiphenyl sulfide; preferably, the mass ratio of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin to the bio-based linear epoxy resin is (0.5-1):(9-9.5).
8. A bio-based epoxy resin / carbon fiber composite material, characterized in that: The composite material is prepared by blending and filling the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin described in claim 1 or the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin prepared by the method described in any one of claims 2-5 with a bio-based linear epoxy resin in a carbon fiber cloth, and then laminating and curing the mixture; before curing, the carbon fiber cloth is modified by a thiol-olefin click reaction using a terminal thiol hyperbranched polymer prepared by the method described in any one of claims 2-5 to obtain a surface functionalized carbon fiber cloth.
9. The bio-based epoxy resin / carbon fiber composite material according to claim 8, characterized in that: The preparation method comprises the following steps: immersing a carbon fiber cloth in a mixed solution of a terminal thiol hyperbranched polymer prepared by any method described in claims 2-5, an organic solvent and a photoinitiator, and performing a thiol-olefin click reaction for 40-80 minutes under the action of the photoinitiator using ultraviolet light with a power of 400W-800W; after the reaction is completed, taking out the carbon fiber cloth, and drying it at 50-80°C for 8-24 hours to obtain a surface functionalized carbon fiber cloth; putting the surface functionalized carbon fiber cloth into a mold, and evenly applying the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin described in claim 1 or a mixture of the hexahydro-s-triazine-containing bio-based hyperbranched epoxy resin prepared by any method described in claims 2-5, a bio-based linear epoxy resin and a curing agent on the surface functionalized carbon fiber cloth, hot pressing and curing for 3-6 hours under the conditions of 1-10MPa and 80-180°C, and taking it out after cooling to room temperature to obtain a bio-based epoxy resin / carbon fiber composite material; Preferably, the mass ratio of the carbon fiber cloth to the terminal mercapto hyperbranched polymer is 1:(0.50-0.83); the mass ratio of the surface functionalized carbon fiber cloth, the hexahydrotriazine-containing bio-based hyperbranched epoxy resin, and the bio-based linear epoxy resin is (0.90-0.95):(0.01-0.05):(0.45-0.50); Preferably, the photoinitiator is one or more of p-aminopropiophenone, 4-dimethylaminopyridine, benzophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and the mass of the added photoinitiator is 1.0-3.5% of the mass of the carbon fiber cloth; the organic solvent is one or more of tetrahydrofuran, 1,4-dioxane, ethyl acetate, anhydrous ethanol, methanol, dimethyl sulfoxide, toluene, xylene, acetone, chloroform, N,N-dimethylformamide and dichloromethane, and its mass is 5 to 30 times the mass of the carbon fiber cloth; the curing agent is one or more of 4,4'-methylenebiscyclohexylamine, 4,4'-diaminodiphenylmethane, diethylenetriamine, isophoronediamine, 2,2'-diaminodiphenyl sulfide and 4,4'-diaminodiphenyl sulfide.
10. A degradation and recycling method for a bio-based epoxy resin / carbon fiber composite material, characterized in that: The method comprises the following steps: immersing the bio-based epoxy resin / carbon fiber composite material according to any one of claims 8 to 9 in an acidic hydrogen peroxide solution, and degrading the bio-based epoxy resin / carbon fiber composite material at 60 to 80° C. for 6 to 12 hours to obtain a carbon fiber cloth and a degradation solution; rinsing the carbon fiber cloth with acetone and drying the carbon fiber cloth at 50 to 70° C. for 10 to 24 hours to obtain a regenerated carbon fiber cloth; Preferably, the acidic hydrogen peroxide solution is a hydrogen peroxide solution of phosphoric acid or hydrochloric acid, the acid concentration is 0.10-1.00 mol / L, the solvent in the acidic hydrogen peroxide solution is one or more of tetrahydrofuran, 1,4-dioxane, acetone, water and N,N-dimethylformamide, and the mass proportion of hydrogen peroxide in the acidic hydrogen peroxide solution is 50%-90%; the mass ratio of the bio-based epoxy resin / carbon fiber composite material to the acidic hydrogen peroxide solution is 1:(2-5).
Citation Information
Patent Citations
Carboxyl-terminated hyperbranched polymers and their applications in the preparation of high-performance plastic composites
CN108084447B
A sulfur-containing biodegradable hyperbranched epoxy resin and its preparation method
CN108794726B
A biodegradable hyperbranched epoxy resin and its preparation method
CN108794727B
Bio-based degradable hyperbranched epoxy resin and preparation method thereof
CN111647137A
Bio-based hyperbranched polymer epoxy resin and preparation method thereof
CN114395216A